Preparation of high‐performance epoxy‐containing silicone rubber via hydrosilylation reaction. Issue 8 (19th August 2019) - Wang, Yuan; Zhang, Bin; Zhou, Shengtai; Chen, Yang; Liang, Mei; Zou, Huawei
ABSTRACT: A novel epoxy‐containing silicone rubber network was constructed by hydrosilylation reaction among the synthesized vinyl‐containing epoxy resin prepolymers, vinyl terminated silicone oil and hydrogen‐containing silicone oil. The structure of the vinyl‐containing epoxy resin prepolymers was characterized by Fourier transform infrared spectroscopy and 1 H nuclear magnetic resonance spectroscopy. Morphology observations revealed that uniform "sea‐island" phase separation structure was present in modified silicone rubbers. The compatibility between silicone rubber and epoxy resin was enhanced, thanks to the good dispersion of vinyl‐containing epoxy prepolymers in silicone rubber matrix. The adhesion and tensile properties of modified silicone rubbers were greatly enhanced when compared with those of unmodified counterparts. The thermal degradation behavior of cured silicone rubbers was studied using thermogravimetric analysis and thermogravimetric/infrared spectrometry analysis. Results showed that the formation of epoxy‐containing silicone rubber network altered the degradation process of silicone rubber, thereby yielding a higher residue at 800 °C under nitrogen atmosphere. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48397. Abstract : Formed network structure.